Integrating pharmaceutical systems strengthening in the current global health scenario: three 'uncomfortable truths' - Tamara Hafner; Marlon Banda; Jillian Kohler; Zaheer-; Murray Lumpkin; Mojisola Christianah Adeyeye; Emmanuel Nfor; Francis Aboagye-Nyame; Javier Guzman (Taylor & Francis Group, 2020)
The response to emergency public health challenges such as HIV, TB, and malaria has been successful in mobilising resources and scaling up treatment for communicable diseases. However, many of the remaining challenges in improving access to and appropriate use of medicines and services require pharmaceutical systems strengthening. Incorporating pharmaceutical systems strengthening into global health programmes requires recognition of a few 'truths'. Systems strengthening is a lengthy and resource-intensive process that requires sustained engagement, which may not align with the short time frame for achieving targets in vertical-oriented programmes. Further, there is a lack of clarity on what key metrics associated with population and patient level outcomes should be tracked for systems strengthening interventions. This can hinder advocacy and communication with decision makers regarding health systems investments. Moving forward, it is important to find ways to balance the inherent tensions between the short-term focus on the efficiency of vertical programmes and broader, longer-term health and development objectives. Global health programme design should also shift away from a narrow view of medicines primarily as an input commodity to a more comprehensive view that recognizes the various structures and processes and their interactions within the broader health system that help ensure access to and appropriate use of medicines and related services.